Proposal of a model for the use of industry 4.0 elements in asset-intensive industries (2022)
The corporate strategy of today's asset-intensive companies faces an interconnected world, which demands management systems that guarantee the fulfillment of all proposed targets in the most efficient way possible. In this context, the concept of Operational Excellence is born, which aims to ensure competitiveness at all levels and departments of an organization on a continuous basis. The adoption of Industry 4.0, I4.0, allows to reach a higher degree of efficiency within the organizational processes that it turns out to be an important ally in achieving this goal. However, one of the main challenges that firms face is the enhancement of digital technologies in their value chain, not only in their missionary processes, but also in management and backup processes. After an extensive literature review, it is evident that there is a lack of tools aimed at management to provide criteria on how to transform their installed capacity. In this line of thinking, this article proposes a model of applicability of I4.0 elements in capital-intensive industries